2001
DOI: 10.1046/j.1439-037x.2001.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Stress on Physiological Attributes and their Relationship with Growth and Yield of Wheat Cultivars at Different Stages

Abstract: The eects of water stress on physiological attributes of drought-sensitive (Kalyansona) and drought-tolerant (C-306) wheat cultivars were studied in a pot experiment. Water stress was imposed by withholding irrigation at boot and anthesis stages. Leaf water potential, leaf osmotic potential and leaf turgor potential (measured with 1 1 pressure chamber and osmometer), as well as leaf diusive resistance, leaf transpiration rate and leaf-to-air transpiration gradient (measured with a steady-state porometer) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 20 publications
8
95
1
2
Order By: Relevance
“…Also Gupta et al (2001) reported that during wheat anthesis period, drought stress reduced stem dry weight, number of grains, 1000 grain weight, grain yield, harvest index and biological yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Gupta et al (2001) reported that during wheat anthesis period, drought stress reduced stem dry weight, number of grains, 1000 grain weight, grain yield, harvest index and biological yield.…”
Section: Resultsmentioning
confidence: 99%
“…Debake et al (1996) demonstrated that imposing stress, especially after anthesis stage, entailed a significant decrease in harvest index. Gupta et al (2001) declared that there was a direct positive relation between biological yield and grain yield. Harvest index is so extremely affected by environmental changes that its value increases under desirable climatic conditions and decreases under drought stress condition at final period of plant growth (Siddique and Whan, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Stress tolerance and susceptibility indices including mean productivity (MP), geometric mean productivity (GMP), tolerance (TOL), drought susceptibility index (DSI) and yield stability index (YSI) for water deficit environment were calculated based on grain yield under sever water stress (50% FC) and unstressed (100% FC). Stress tolerance attributes were calculated by the following formulae: Mean productivity (MP) and Tolerance (TOL) was calculated according to Gupta et al (2001 Chaudhuri and Kanemasu (1982) where, Ys = mean yields of a given genotype in WS (50% FC) condition; Yp = mean yields of a given genotype in NS (100% FC) condition; DII = Drought intensity index. The drought intensity index (DII) for each water regime was calculated as DII =1 -Xs/X p Genotyping DNA Genomic DNA was extracted following the phenol-chloroform method of Pallotta et al (2000) with some minor modifications.…”
Section: Tolerance Indicesmentioning
confidence: 99%
“…Also, they reported agronomic traits such as grain yield and its components are the major selection criteria for evaluating drought tolerance under field condition. Gupta et al (2001) studied physiological and yield attributes of two wheat genotypes with stress at boot and anthesis. They indicated that number of grains, grain yield, biological yield, and harvest index decreased to a greater extent when water stress was imposed at anthesis stage.…”
Section: Crop Sampling and Calculationmentioning
confidence: 99%